Tecnologias no livro didático de Ciências e prática docente: Superando os desafios na formação continuada - Oliveira, Aridelson Joabson Almeida de (2019)
The Digital Information and Communication Technologies (DICT) in contemporary society influence daily relations in the various social sectors, including in the educational sector. The insertion of technologies in the classroom is still a new environment to be explored, under a new perspective as a new pedagogical resource. So, this research intends to evaluate the didactic-pedagogical contributions coming from a continuous training in the form of mini- course, provided to Science teachers in the city of Esperança - PB, about the uses of the DICT in the classroom. The research is based on the educational contributions coming from theorists such as Vygotsky, Freire, Tardif, Nóvoa and Moran, constructed as a field research, qualitative, of an exploratory nature, with analytic categorization cuts in Bardin. The mini- course took place in four stages, (i) probing the expectations of teachers about DICT through a questionnaire; (ii) analysis of the DICT in the Didactic Book of Science (DBS); (iii) performance of the mini-course; (iv) application of the mini-course evaluative questionnaire. It should be noted that technological resources should be (re) known to educators as pedagogical tools that facilitate teacher making, especially. The study shows that there is a deficit in the initial formation of Science teachers, especially with those who have been in the teaching profession for a longer time, but the presentation of the technologies as a pedagogical resource in planning, teaching and evaluation has brought contributions to teachers. The mini-course carried out may show that the available technologies are not so difficult to use and that seeking training is necessary to act in the classroom. Educational institutions, whether academic or regular, should invest in initial and continuing education of educational professionals by prioritizing educational proposals with the DICT. However, technologies are not salvation for education, but can be an effective resource in the learning process, making it easier to plan and streamline the classroom, in the teaching profession and/or in the evaluation processes.